The Importance Of Working On Sentences In The Development Of Oral And Written Speech Of Primary Class Students (Eurasian Journal of Learning and Academic Teaching, 2023)
This article provides an idea of the importance of working on a sentence in the cultivation of oral and written speech of Primary School students and the role of tone in the formation of a sentence.